Stability-indicating RP-HPLC method for simultaneous quantitation of tramadol and aceclofenac in presence of their major degradation products: Method development and validation. Issue 17 (21st October 2017) - Gousuddin, Md.; Sengupta, Pinaki; Chatterjee, Bappaditya; Das, Sreemoy Kanti
ABSTRACT: Primary objective of this study was to develop a stability-indicating reverse-phase high-performance liquid chromatography (HPLC) method for simultaneous quantitation of tramadol and aceclofenac in presence of their degradation products. The drugs were subjected to various International Conference on Harmonization recommended stress conditions, such as acid hydrolysis, alkaline hydrolysis, peroxide oxidation, thermolysis, and photolysis. The major degradation products got well resoluted from the analytes in HPLC analysis with a mobile phase composed of a mixture of 0.01 M ammonium acetate buffer (pH 6.5) and acetonitrile (65:35, v/v) through a Phenomenex Gemini C18 (250 mm × 4.6 mm, 5 µm particle size) column. The method was linear over a range of 15–60 µg/mL for tramadol and 40–160 µg/mL for aceclofenac concentration. The analytes were detected at a wavelength of 270 nm. The method was validated and found to be specific, accurate, precise, stable, and robust for its intended use. The method can be recommended for its future use in routine quality control, accelerated and real-time stability analysis of the formulations containing tramadol and aceclofenac combination. GRAPHICAL ABSTRACT: